1997
DOI: 10.1038/bjc.1997.503
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and specific detection of P-glycoprotein function for haematological and solid tumour cells using a novel nucleic acid stain

Abstract: Summary Progress in our understanding of the contribution of P-glycoprotein (P-gp)-mediated resistance to chemotherapy failure in haematological as well as solid tumours has been hampered by the lack of highly sensitive, reliable methods for the detection of P-gp function in fresh human tumour cells. The present study identifies the novel nucleic acid stain SYT016 as a highly sensitive and specific dye to assess P-gp function. The effect of P-gp is expressed here as the ratio of dye fluorescence (RF) from cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 12 publications
(18 reference statements)
1
36
0
Order By: Relevance
“…Kuhnel et al (8) have also found a higher sensitivity of the red fluorescence of JC-1 for the changes in P-gp activity. Several other P-gp substrates are being used for the evaluation of P-gp activity: Rh 123, Calcein-AM (Ca-AM), Syto 16 (9,12,17). So far none of them has been described as a substrate specific for P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…Kuhnel et al (8) have also found a higher sensitivity of the red fluorescence of JC-1 for the changes in P-gp activity. Several other P-gp substrates are being used for the evaluation of P-gp activity: Rh 123, Calcein-AM (Ca-AM), Syto 16 (9,12,17). So far none of them has been described as a substrate specific for P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…This results in steady state cellular accumulation. 25 Incubation was carried out in the presence or absence of 1 m PSC833 to check the effect of P-glycoprotein activity on Syto R 16 accumulation. 25 After washing in PBS/BSA the fluorescence was recorded using flow cytometry.…”
Section: Apoptosis Detectionmentioning
confidence: 99%
“…25 In addition, recently Frey 12 has shown that Syto dyes can be used to detect apoptosis probably by detection of changes in the structure of DNA and/or RNA. Since plasma membrane changes are among the earliest changes in the apoptotic process, in the present study the question addressed was whether Syto R 16 might be able to detect an early phase of apoptosis, characterised among others by P-glycoprotein activity changes.…”
mentioning
confidence: 99%
“…They exhibit very low inherent fluorescence, with strong enhancement upon binding to DNA/ RNA. SYTO-stained eukaryotic cells display both nuclear and diffuse cytoplasmic staining pattern (17,18), the latter shown to be abolished after formaldehyde fixation (19). DNA binding properties of SYTO dyes have been exploited to visualize characteristic nuclear morphology during apoptosis or even to assess level of DNA synthesis after exposure to endocrine disrupting chemicals (18,20,21).…”
mentioning
confidence: 99%
“…It should be noted, however, that SYTO probes are not exclusive DNA stains, and thus several of them have been successfully applied to visualize translocation of RNA granules in neurons and allow differential discrimination of nuclear/mitochondrial DNA from cytoplasmic RNA using two-photon lifetime imaging (17,22). Importantly recent reports suggest the reliability of some SYTO dyes as effective substrates in quantitative P-glycoprotein (P-gp) function assessment (14,19,23).…”
mentioning
confidence: 99%